Cisplatin encapsulation within a ferritin nanocage: a high-resolution crystallographic study. Issue 22 (18th February 2016) - Pontillo, Nicola; Pane, Francesca; Messori, Luigi; Amoresano, Angela; Merlino, Antonello
Abstract : Cisplatin (CDDP) can be encapsulated within the central cavity of reconstituted (apo)ferritin, (A)Ft, to form a drug-loaded protein of potential great interest for targeted cancer treatments. Abstract : Cisplatin (CDDP) can be encapsulated within the central cavity of reconstituted (apo)ferritin, (A)Ft, to form a drug-loaded protein of potential great interest for targeted cancer treatments. In this study, the interactions occurring between cisplatin and native horse spleen Ft in CDDP-encapsulated AFt are investigated by high-resolution X-ray crystallography. A protein bound Pt center is unambiguously identified in AFt subunits by comparative analysis of difference Fourier electron density maps and of anomalous dispersion data. Indeed, a [Pt(NH3 )2 H2 O] 2+ fragment is found coordinated to the His132 residue located on the inner surface of the large AFt spherical cage. Remarkably, Pt binding does not alter the overall physicochemical features (shape, volume, polarity/hydrophobicity and electrostatic potential) of the outer surface of the AFt nanocage. CDDP-encapsulated AFt appears to be an ideal nanocarrier for CDDP delivery to target sites, as it possesses high biocompatibility and can be internalized by receptor mediated endocytosis, thus carrying the drug to tumor tissue with higher selectivity than free CDDP.